Miasto i jego ukryty wymiar w sztuce - Koniecko, Remigiusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
The City and its hidden dimension in art The purpose of this article is to show the relationship between art, photography and architectural spaces that create new creative visions in these areas. The explored topic reveals a situation that affects the understanding of the current role of architecture, where previously there was no place for abstract concepts. Today this gap is complemented by artists as well as by architects, who often straddle architectural practice and a desire to be an artist. The penetration of these attitudes creates a situation in which the previously outlined boundaries of both disciplines are being crossed, in what might be called the transgression of art and architecture. As a result, a relationship between an artist and a given space is created. But what effect has this on the understanding of the relationship? What can we learn from these relationships?